PERIODE KRITIS TANAMAN CABAI MERAH BESAR (CAPSICUM NNNUUM L. VAR. LONG CLTILLI) PADA PERLAKUAN CEKAMAN AIR - Widiyono, W.; Hidayati, Nuril (Perhimpunan Biologi Indonesia, 2005)
ABSTRACTThe critical period of red chili (Capsicum annuum L. var. long chili) under water stresstreatment. The research of the effect of water stress to the morphological characters of redchili was conducted to understand the critical period of vegetative stage. The experiment wasarranged based on Randomized Complete Block Design, consist of 14 water treatments with 3replications. Stressed plants were watered 500 ml each week at stress period and no stressedplants were watered 1500 ml each week. On the first weeks all samples were watered in fieldcapacity. The treatments i.e. Control plants were watered during 1-14 weeks; Plants weretreated in stress period respectively at ages 2 weeks; 2-3 weeks; 2-4 weeks; 2-5 weeks; 2-6weeks; 2-7 weeks and continued watering; Plants were watered at field capacity during 2-7weeks, 2-6 weeks; 2-5 weeks; 2-4 weeks; 2-3 weeks and 2 weeks, and continued stressperiod treatment; Plants were treated in stress period during 2-1 4 weeks. The result showedthat (i). Water stress treatments were significantly increase roots length; reduce length andweigl t of stem; number, area and weight of leave. (ii). Red chili plants at vegetative stagewere more resistant to water stress compared with reproductive stage according to stem andleave parameters.Keywords: Critical period, water stress, Capsicum annuum L. var. long chili